Isolated pulmonary interstitial glycogenosis associated with alveolar growth abnormalities: A long‐term follow‐up study. Issue 6 (25th March 2019) - Sardón, Olaia; Torrent‐Vernetta, Alba; Rovira‐Amigo, Sandra; Dishop, Megan K.; Ferreres, Joan Carles; Navarro, Alexandra; Corcuera, Paula; Korta‐Murua, Javier; Peña, Pilar García; Pérez‐Belmonte, Elena; Villares, Ana; Camats, Núria; et al.
Abstract: Introduction: Pulmonary interstitial glycogenosis (PIG) is a rare infant interstitial lung disease characterized by an increase in the number of interstitial mesenchymal cells, presenting as enhanced cytoplasmic glycogen, and is considered to represent the expression of an underlying lung development disorder. Methods: This study describes the clinical, radiological, and functional characteristics and long‐term outcomes (median 12 years) of nine infants diagnosed with isolated PIG associated with alveolar simplification in the absence of other diseases. Results: All patients presented with tachypnea. Additionally, seven patients had breathing difficulties and hypoxemia. Abnormalities in chest‐computerized tomography (CT) with a pattern of ground‐glass opacity, septal thickening, and air trapping were observed in all individuals, with images suggesting abnormal alveolar growth (parenchymal bands and architectural distortion). All lung biopsies showed alveolar simplification associated with an increased number of interstitial cells, which appeared as accumulated cytoplasmic glycogen. In the follow‐up, all patients were asymptomatic. The respiratory function test was normal in only two patients. Five children showed an obstructive pattern, and two children showed a restrictive pattern. Chest‐CT, performed after an average of 6.5 years since the initial investigation, revealed a partial improvement of the ground‐glass opacity pattern; however, relevant alterations persisted. Conclusion: Although the patients with PIG in the absence of other associated pathologies had a good clinical outcome, significant radiographic alterations and sequelae in lung function were still observed after a median follow‐up of 12 years, suggesting that PIG is a marker of some other persistent abnormalities in lung growth, which have effects beyond the symptomatic period.